Increased Valency of Conserved-mosaic Vaccines Enhances the Breadth and Depth of Epitope Recognition - Abdul-Jawad, Sultan (Mol Ther, 2016)
The biggest roadblock in development of effective vaccines against human immunodeficiency virus type 1 (HIV-1) is the virus genetic diversity. For T-cell vaccine, this can be tackled by focusing the vaccine-elicited T-cells on the highly functionally conserved regions of HIV-1 proteins, mutations in which typically cause a replicative fitness loss, and by computing multivalent mosaic proteins, which maximize the coverage of potential 9-mer T-cell epitopes of the input viral sequences. Our first conserved region vaccines HIVconsv employed clade alternating consensus sequences and showed promise in the initial clinical trials in terms of magnitude and breadth of elicited CD8(+) T-cells. Here, monitoring T-cells restricted by HLA-A*02:01 in transgenic mice, we assessed whether or not the tHIVconsv design (HIVconsv with a tissue plasminogen activator leader sequence) benefits from combining with a complementing conserved mosaic immunogen tHIVcmo, and compared the bivalent immunization to that with trivalent conserved mosaic vaccines. A hierarchy of tHIVconsv ≤ tHIVconsv+tHIVcmo < tCmo1+tCmo2+tCmo3 vaccinations for induction of CD8(+) T-cell responses was observed in terms of recognition of tested peptide variants. Thus, our HLA-A*02:01-restricted epitope data concur with previously published mouse and macaque observations and suggest that even conserved region vaccines benefit from oligovalent mosaic design.